Novos Veios da Literatura Comparada: Imagologia e estereótipos em Le Clézio, Lídia Jorge e Fay Weldon - Simões, Maria João (2010)
Novos Veios da Literatura Comparada: Imagologia e estereótipos em Le Clézio, Lídia Jorge e Fay Weldon”